A path toward the clinical translation of nano‐based imaging contrast agents. (2nd May 2021) - Miyasato, Dominie L.; Mohamed, Ahmed W.; Zavaleta, Cristina
Abstract: Recently, nanoparticles have evolved ubiquitously in therapeutic applications to treat a range of diseases. Despite their regular use as therapeutic agents in the clinic, we have yet to see much progress in their clinical translation as diagnostic imaging agents. Several clinical and preclinical studies support their use as imaging contrast agents, but their use in the clinical setting has been limited to off‐label imaging procedures (i.e., Feraheme). Since diagnostic imaging has been historically used as an exploratory tool to rule out disease or to screen patients for various cancers, nanoparticle toxicity remains a concern, especially when introducing exogenous contrast agents into a potentially healthy patient population, perhaps rationalizing why several nano‐based therapeutic agents have been clinically translated before nano‐based imaging agents. Another potential hindrance toward their clinical translation could be their market potential, as most therapeutic drugs have higher earning potential than small‐molecule imaging contrast agents. With these considerations in mind, perhaps a clinical path forward for nano‐based imaging contrast agents is to help guide/manage therapy. Several studies have demonstrated the ability of nanoparticles to produce more accurate imaging preoperatively, intraoperatively, and postoperatively. These applications illustrate a more reliable method of cancer detection and treatment that can prevent incomplete tumor resection and incorrect assessment of tumor progression following treatment. The aim of this review is to highlight the research that supports the use of nanoparticles in biomedical imaging applications and offer a new perspective to illustrate how nano‐based imaging agents have the potential to better inform therapeutic decisions. This article is categorized under: Diagnostic Tools > In Vivo Nanodiagnostics and Imaging Abstract : A path toward clinical translation of nano‐based molecular imaging strategies. Nanoparticle type and delivery considerations for reduced toxicity and accelerated clinical translation of nano‐based contrast agents for imaging.